« De la bêtise et du conformisme » comme forme de stéréotype dans la littérature de Belinda Cannone - Malela, Buata B. (Romanica Silesiana, 2021)
In this paper, our analysis will focus on the concept of stereotype based on the notion of “bêtise” (stupidity) that French essayist and novelist Belinda Cannone deplores. We will study how she rethinks the “bêtise”, after Flaubert who defined it as the art of wanting to conclude. In La bêtise s’améliore (2007) Cannone gives the example of Flaubert, making the “bêtise” the doxa that touches all areas of social life. The central element of “bêtise”, according to Belinda Cannone, remains in many respects conformism. It is a question of seeing how, in Cannone’s discourse, these two notions – “bêtise” and conformism – are articulated and allow her to redefine her ethos of the engaged intellectual in the public space.